Panpsychism and speculative evolutionary aesthetics in Samuel Butler's 'The Book of the Machines'. Issue 2 (1st February 2021) - Danta, Chris
ABSTRACT: Panpsychism is 'the theory or belief that there is an element of consciousness in all matter'. An ancient idea in Western philosophy that predates the earliest writings of the pre-Socratics, panpsychism is currently being revived in a number of different disciplines in the humanities. One reason for this resurgence of interest in panpsychism in the contemporary humanities is that panpsychism mitigates human exceptionalism by reconnecting us with the various elements of our nonhuman environment, both animate and inanimate. In this essay, I show how Samuel Butler's fiction is relevant to the contemporary revival of panpsychism in the humanities by illustrating how Butler uses panpsychism in his 1872 novel Erewhon to speculate that machines might one day gain consciousness. Making Butler's treatment of what David Chalmers calls the 'hard problem of consciousness' in Erewhon so aesthetically rich, I argue, is the fact that he constructs various speculative evolutionary scenarios in the text that challenge his reader's preconceptions of what consciousness is. I label Butler's approach to the problem of mitigating human exceptionalism in Erewhon speculative evolutionary aesthetics.